Influence of Monstera riedrichsthalii bionic textures on the tribological and vibration behavior of rolling bearings - Risheng Long; Qingyu Shang; Shaoni Sun; Siwei Wang; Chi Ma; Jianwei Zhang; Max Marian (Friction)
Surface texturing has been proven to be an effective method for improving the lubrication characteristics and tribological behavior of tribo-pairs under various operating conditions. Inspired by the unique Swiss cheese-like leaves of Monstera riedrichsthalii, eight bionic texture patterns were introduced. The influence of vein features, such as costal vein angles (45° and 60°), vein symmetry (symmetric, asymmetric), and elliptical holes, on the tribological and vibration characteristics of rolling bearings was investigated under starved lubrication through a wear test rig and time‒frequency domain vibration signal analysis. The results show that the average coefficients of friction and wear losses of the Monstera riedrichsthalii bionic-textured groups are generally lower than those of the smooth reference. The amplitudes and parameters (i.e., peak value, root mean square (RMS), and crest factor) of the time-domain vibration signals of the textured groups are greater than those of the smooth group in the early stages, but the vibration parameters of most textured groups are lower than those of the smooth bearings in the later stages, especially those of the groups with elliptical holes. The amplitudes and power spectral density (PSD) curves of the frequency-domain vibration signals exhibit similar variations to those of the time-domain signals. Compared with the smooth reference, the Monstera riedrichsthalii bionic-textured group with a combination of 45° secondary-vein angle, asymmetry, and elliptic holes can provide excellent tribological and vibration performance. Its well-lubricating period, average coefficient of friction (CoF), and mass loss can be effectively prolonged or reduced by 37.4%, 7.3%, and 43.9%, respectively.